Age-Dependent Decrease in Serum Transforming Growth Factor (TGF)-Beta 1 in Healthy Japanese Individuals; Population Study of Serum TGF-Beta 1 Level in Japanese. Issue 2 (9th June 2013) - Okamoto, Yoshihiro; Gotoh, Yoshimitsu; Uemura, Osamu; Tanaka, Soichi; Ando, Tsunesaburo; Nishida, Mikio
Abstract : Transforming growth factor-beta1 (TGF- β 1), a multi-functional cytokine, is involved in regulating a variety of cellular activities and the serum/plasma TGF- β 1 level is altered with various diseases. However, most published reports have described adult patients, and so we investigated the clinical significance of serum TGF- β 1 level in pediatric patients. The diagnostic application of the measurement of serum TGF- β 1 level depends critically on the control value, however, there is no information on the control value of serum TGF- β 1 for children. In the present study, we determined the serum TGF- β 1 level of healthy Japanese children as a control value with enzyme-linked immunosorbent assay (ELISA). The serum TGF- β 1 level of children (0–14 years old) was significantly higher than that of adults (over 15 years old) ( p < 0.01). Thus, it is recommended that when the serum TGF-β1 levels of patients are evaluated, they should be compared with those of age-matched controls.